Atomic force microscopy : biomedical methods and applications - Braga, Pier Carlo, Ed. Ricci, Davide, Ed (Methods in molecular biology (Clifton, N.J.), v. 242, 2004)
Provides biomedical researchers the hands-on knowledge for using atomic force microscopy in their research. It offers many benefits including high manification with high resolution, minimal tissue or cell preparation, the ability to obtain different views of the sample from a single data collection, and the ability to study live cells in their physiologic environment. The authors begin with an introduction on the basics of atomic force microscopy and then covers specific protocols for the morpho-structural analysis of cellular structures. Also covered are detailed protocols for investigating subcellular structures and the latest techniques for functional investigations using AFM. The 28 chapters should prove to be an essential laboratory manual for all scientists using atomic force microscopy in their biomedical research.